Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Gia Hân

Bài 3 : (2 điểm) Tìm x

a) 6x2 – (2x – 3)(3x + 2) = 1

b) (x+1)3– (x – 1)( x2+ x + 1) – 2 = 0

Xyz OLM
21 tháng 11 2021 lúc 15:21

6x2 - (2x - 3)(3x + 2) = 1

<=> 6x2 - (6x2 - 5x - 6) = 1

<=> 5x  + 6 = 1

=> 5x = -5

=> x = -1

Vậy x = -1

Khách vãng lai đã xóa
Xyz OLM
21 tháng 11 2021 lúc 15:21

b) (x + 1)3 - (x - 1)(x2 + x + 1) - 2  = 0

<=> x3 + 3x2 + 3x + 1 - (x3 - 1) - 2 = 0

<=> 3x2 + 3x = 0

<=> 3x(x + 1) = 0

<=> x(x + 1) = 0

<=> \(\orbr{\begin{cases}x=0\\x=-1\end{cases}}\)

Vậy \(x\in\left\{0;-1\right\}\)

Khách vãng lai đã xóa

\(a\text{)}6x^2\left(2x-3\right)\left(3x+2\right)=1\)

\(\Leftrightarrow6x^2-\left(6x^2-5x-6\right)=1\)

\(\Leftrightarrow5x+6=1\)

\(\Leftrightarrow5x=\left(-5\right)\)

\(\Rightarrow x=-1\)

\(b\text{)}\left(x+1\right)^3-\left(x-1\right)\left(x^2+x+1\right)-2=0\)

\(\Leftrightarrow x^3+3x^2+3x+1-\left(x^3-1\right)-2=0\)

\(\Leftrightarrow3x^2+3x=0\)

\(\Leftrightarrow3x\left(x+1=0\right)\)

\(\Leftrightarrow x\left(x+1\right)=0\)

\(\Leftrightarrow x=0;x=\left(-1\right)\)

\(\Rightarrow x\in\left\{0;-1\right\}\)

\(\text{Hok tốt!}\)

\(\text{@Kaito Kid}\)

Khách vãng lai đã xóa

Các câu hỏi tương tự
Nguyễn Thị Chuyên
Xem chi tiết
Kiều Nguyễn Linh Ánh
Xem chi tiết
Nguyễn Hữu Quang
Xem chi tiết
nguyễn hồng trang
Xem chi tiết
Tuyết Ly
Xem chi tiết
43-LÊ XUÂN ANH VIỆT-8A5
Xem chi tiết
quangvinh
Xem chi tiết
cù thị lan anh
Xem chi tiết
Anh Phạm Phương
Xem chi tiết